Effect of individual and combined supplementation of vitamin E and selenium on the performance of broiler chicks fed ochratoxin - A - PRAKASH, K; UMAKANTHA, B; DEVEGOWDA, G; GOWDH, C V; KRISHNAPPA, G (The Indian Journal of Animal Sciences, 2013)
An experiment with a completely randomized block design was used to evaluate the effects of ochratoxin (2 mg/kg of diet), vitamin E (400 mg/kg) and selenium (1 mg/kg), both individually and in combination, in 6 week old broilers. Commercial broilers (240) were randomly placed in battery brooder with 10 birds/pen. Each treatment was replicated 3 times. A significant (P<0.05) drop in body weight, total protein and increase in mortality, relative weights of kidney, liver, serum uric acid and gamma glutamyl transferase activity were noticed. Mortality was highest among the broiler fed OA. Addition of selenium alone did not alter any of the parameters evaluated. Vitamin E alone and in combination with selenium significantly (P <0.05) diminished the growth inhibitory effect of OA, reduced the liver weight, severity of hepatie lesions and reduced the activity of GGT to control level. The increase in uric acid and decrease in total serum protein values caused by OA were significantly diminished to differing degree by vitamin E plus selenium, These data suggest that vitamin E alone or in combination with selenium can modulate the toxicity of OA in broilers.